The reality of practicing physical education and sports in the primary stage )Descriptive study conducted by some elementary schools of Southern Medea - Boudali , adel; bensassi , radhouane; medjadi , rabeh (sports creativity, 2025)
This study aims to identify the reality of practicing physical education and sports in the primary phase in some primary schools in the southern state of Medea, and to achieve the objectives of the study, we followed the descriptive approach, where the study sample reached 50 primary education teachers who were deliberately chosen and we used a questionnaire form as a tool to collect data and this form consists of 9 questions And three axes, and after statistical treatment, presenting the results, analyzing and interpreting them, it was concluded that the physical education and sports class is a neglected subject of practice in this primary phase.